Exosome-mediated stable epigenetic repression of HIV-1 - Surya Shrivastava (Nature Portfolio, 2021)
A strategy to control HIV-1 infection is to stably repress HIV-1 and induce “deep latency”. Here the authors show that a recombinant anti-HIV-1-1 protein can be packaged as mRNA into exosomes and delivered systemically to repress HIV-1-1 within the context of virus infected mice and achieve long term silencing of HIV-1-1 expression.